The perspective of ethanol as a lawful component in alcohol-based perfumes through fiqh and science point of view - Putri, Tanti Amarta (Journal of Halal Product and Research (JHPR), 2022)
The COVID-19 pandemic forces citizens of Indonesia to live off micro, small, and medium enterprises (SME's) as a way to earn money. Looking at the reality around us, SME's that thrive are ones that sell food and drinks, although perfumery can also be easily found. However, a problem emerges from this. Being a country with mostly Muslim citizens, citizens become more worried and need reassurance that what they are faced with is a permissible (halal) product. Not only do they insist on the sellers, but these citizens also need the government to inspect the sale of alcohol-based perfumes. This article collects and composes data with an article or journal reviewing method and the guidance of certified scholars. Therefore, it is important to discover the permissibility of alcohol-based products used for external use, such as perfume, from fiqh and science. It was found that the composition of perfume is not khamr thus not filthy (najs) to be worn.